Functional outcome and health related quality of life after dual mobility cup total hip replacement for displaced femoral neck fractures in middle aged Egyptian patients. Issue 3 (March 2018) - Rashed, Ramy Ahmed; Sevenoaks, Hannah; Shabaan, Amira Mohammed; Choudry, Qaisar Akhlaq; Hammad, Abdullah Said; Kasem, Mohammed Samir; El Khadrawe, Tarek Aly; El Dakhakhny, Magdy Mohammed
Abstract: Aim: This study was done to assess the functional and clinical results after one year of cemented THR with dual mobility cup for the treatment of fracture neck femur in active middle-aged patients in Egypt (Middle Eastern population). Patients and methods: This study included 31 patients (32 hips) with displaced femoral neck fractures that were admitted to El Hadara University Hospital, Alexandria, Egypt. Their mean age was 66.4 ± 5.9 years. Fifteen patients were females. All the patients were treated with total hip replacement using a cemented dual mobility cup (Ecofit ® 2 M, Implantcast GmbH, Germany) total hip replacement through the standard posterior approach. Functional assessment was done using Harris Hip Score (HHS), SF-36 questionnaire for health related quality of life (HRQoL) with assistance of a physiotherapist. Results: The mean HHS improved over the follow up period from 79.04 ± 7.9 at 12 weeks to an average of 92.8 ± 11.1 at 1 year follow up. HRQoL measures showed a pattern of initial drop at 3 months postoperatively, then a steady rise to be restored at 1 year as compared to the preoperative baseline measures. There were no dislocations encountered in this series over one year follow up. The following complications were encountered; 1 deep infection, 2 deep vein thrombosis, 2 heterotopic ossifications, and 1 patient died within one year after surgery. Conclusions: Dual mobility cup total hip replacement is an acceptable method for treatment of displaced femoral neck fracture in active middle aged patients in Egypt as it provides pain relief and good function without compromising the stability.